Biophysical and socioeconomic factors influencing soil carbon stocks: a global assessment. Appendix S1: Raw Dataset [Conjunto de datos] - Duarte Guardia, Sandra; Peri, Pablo Luis; Amelung, Wulf; Thomas, Evert; Borchard, Nils; Baldi, Germán; Cowie, Annette L.; Ladd, Brenton (Grupo de Investigación Forestal-Silvopastoril. Instituto Nacional de Tecnología Agropecuaria (INTA), EEA Santa Cruz; Universidad Nacional de la Patagonia Austral (UNPA); Centro Austral de Investigaciones Científicas (CADIC-CONICET)., 2021)
Supplementary information of the: Duarte-Guardia, S., Peri, P., Amelung, W. et al. Biophysical and socioeconomic factors influencing soil carbon stocks: a global assessment. Mitig Adapt Strateg Glob Change 25, 1129–1148 (2020).